Simulation of the Optimum Planting Windows for Early and Intermediate-Maturing Maize Varieties in the Nigerian Savannas Using the APSIM Model - Beah, Aloysius; Kamara, Alpha Yaya; Jibrin, Jibrin Mohamed; Akinseye, Folorunso Mathew; Tofa, Abdullahi Ibrahim; Ademulegun, Temitope Damian (Frontiers in Sustainable Food Systems, 2021)
The Agricultural Production systems simulator (APSIM) model was calibrated and evaluated and used to identify the optimum planting windows for two contrasting maize varieties for three agro-ecologies in the Nigeria savannas. The model accurately simulated growth and yield of maize grown in the Guinea and Sudan savannas of Nigeria. The planting date analysis showed that optimum planting windows for 2009EVDT and IWDC2SynF2, depend on the variety, agro-ecozones and sites. Planting from June 15-28 gave the highest yield for both varieties in all the agro-ecologies. In the southern Guinea savanna (SGS) where the length of growing season is 180-210 days, the best planting window was June 15 to July 19 for 2009EVDT and June 15 to July 26 for IWDC2SynF2 in Abuja. In Yelwa, the planting window that gives desirable yield is June 15 to July 5 for 2009EVDT and June 15 - 28 for IWDC2SynF2. In the northern Guinea savanna (NGS) where the length of growing season is 150-180 days, the optimum planting window is June 15 to July 19 for both varieties in Zaria and June 15 to July 19 for 2009EVDT and June 15 to August 2 for IWDC2SynF2 in Sabon Gari. In the Sudan savanna (SS) where the growing season is 90-120 days, planting of 2009EVDT can be delayed up to the third week of July. For the medium-maturing variety, IWDC2SynF2, planting should be done by the first week of July. Though Yelwa is in the SGS, lower yields and narrower sowing windows were simulated for both varieties than for those of the other locations. This is probably due to the poor soil fertility in this location.